Implementation of Regional PEN Loans and Their Impact on The Absorption of Labor in The Regions - irfan sofi; Moza Pandawa Sakti; Arioma Bachtiar; Septian P. Nugraha (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2022)
The Covid-19 pandemic has reduced regional income, thus impacting the implementation of several planned activities in 2020. The Central Government provides funding assistance in the form of Regional Loans for National Economic Recovery. The purpose of this articel is to determine the impact of 2020 Regional National Export Development Loans on Economic Recovery in the Regions, especially on employment. This study uses a combination method. The results of the study found that the 2020 Regional National Export Development Loan had a positive impact on regional economic recovery. Support for the increase in the average capital expenditure which fell by 2.33 times greater for the regions, projects financed from regional PEN loans have maximized the use of local labor to reduce unemployment due to the Covid-19 Pandemic.